Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

Changing Drip Fertigation Strategy to Decrease Greenhouse Agroecosystem Soil Nitrate Residue and Improve Tomato Production in Northwest of China - You Wu; Jiale Zhang; Shicheng Yan; Wei Si; Rui Liu; Jianhua Yang; Zhenxin Qiu; Junliang Fan; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Lung microbiota participated in fibrous microplastics (MPs) aggravating OVA-induced asthma disease in mice - Qian Wu; Rui Li; Yifei You; Wei Cheng; Yan Li; Yan Feng; Yuqin Fan; Yan Wang (Food and Chemical Toxicology, 2024)

Isolation, identification and transcriptome analysis of triadimefon-degrading strain Enterobacter hormaechei TY18 - Yan Wang; Qi Guan; Wenhui Jiao; Jiangbo Li; Rui Zhao; Xiqian Zhang; Weixin Fan; Chunwei Wang (Biodegradation, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

Changes in the lithosphere, atmosphere, and ionosphere before and during the Mw = 7.7 Jamaica 2020 earthquake - Dedalo Marchetti; Kaiguang Zhu; Alessandro Piscini; Essam Ghamry; Xuhui Shen; Rui Yan; Xiaodan He; Ting Wang; Wenqi Chen; Jiami Wen; Yiqun Zhang; Yuqi Cheng; et al. (Remote Sensing of Environment, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Boric acids decorated polymers with Au nanoparticle anchor assisted laser desorption/ionization for qualitive and quantitative analysis of hydroxytyrosol in red wines - Xiaohui Huang; Baichun Wang; Rui Zhai; Chuan-Fan Ding; Xiang Fang; Xinhua Dai; Yinghua Yan (Food Chemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)